Analisis Strategi Sekolah dalam Meningkatkan Prestasi Siswa di Bidang Akademik dan Non-Akademik - Buulolo, Yustina; Zebua, Fentri; Waruwu, Rejois; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
Improving the quality of schools requires various strategies. One of the things that affects students' academic and non-academic abilities is influenced by the strategies used by the principal. The purpose of this research is to find out what are the school strategies in improving students' abilities in the academic and non-academic fields. This study uses a qualitative approach with a descriptive method. The data source used in this study is primary data. The subjects in this study are school principals, teachers, and students. Meanwhile, the object of this study is the analysis of school strategies in improving student achievement. The instruments used in this study are questionnaires for students and interview sheets. The data analysis techniques used are data reduction, data presentation and conclusion. The results of the data analysis showed that school strategies had a positive effect on the development of potential in students, both in the academic and non-academic fields. This is evidenced by the average score of the questionnaire which reached 91.8. The findings of this research are to improve student achievement in the academic and non-academic fields can be done by making policies, programs and activities adjusted to the vision, mission and goals of the school as a basis in determining strategies that can be implemented by all students, as well as utilizing various appropriate media and learning methods so that students are able to be motivated to learn